Mid-term and long-term results of restoring rotation center in revision hip arthroplasty - Zhang, Heng (J Orthop Surg Res, 2020)
BACKGROUND: To restore rotation center exactly in revision hip arthroplasty is technically challenging, especially in Paprosky type III. The technical difficulty is attributable to the complicated acetabular bone defect. In this study, we discussed the method of restoring rotation center in revision hip arthroplasty and reported the clinical and radiological outcome of mid-term and long-term follow-up. METHODS: This study retrospectively reviewed 45 patients (48 hips) who underwent revision hip arthroplasty, in which 35 cases (35 hips) were available for complete follow-up data. During the operation, the acetabular bone defect was reconstructed by impaction morselized bone graft, and the hip rotation center was restored by using remnant Harris fossa and acetabular notches as the marks. The clinical outcome was assessed using the Harris hip score. Pelvis plain x-ray was used to assess implant migration, stability of implants, and incorporation of the bone graft to host bone. RESULT: The average follow-up duration was 97.60 months (range 72–168 months). The average Harris hip score improved from 29.54 ± 10.87 preoperatively to 83.77 ± 5.78 at the last follow-up. The vertical distance of hip rotation center measured on pelvis x-ray was restored to normal, with the mean distance (15.24 ± 1.31) mm (range 12.4~17.3 mm). The mean loss of vertical distance of hip rotation center was (2.21 ± 0.72) mm (range 1.1 ~ 5.3 mm) at the last follow-up. CONCLUSION: Satisfactory clinical and radiological outcome can be obtained through restoring hip rotation center by using remnant Harris fossa and acetabular notches as the anatomical marks in revision hip arthroplasty.